A new Iberian Epigraph with a Latin Anthroponym from Libisosa (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
This article presents an Iberian epigraph recovered in a gentilic worship complex dated in the 2nd century BC. The inscription, engraved on the reverse of a locally produced plate typical of the Ibero-Roman phase of Libisosa, is in North-Eastern writing system, differing from the other published epigraphs from this same site, which use South-Eastern script. The reading, uikaniban, allows us to propose its segmentation in two elements, resulting in an initial segment which, although it may hold a Celtic name, we interpret as the genitive of the Latin cognomen Vicanus, perhaps a member of the increasingly self-romanized Libisosan elite that participated in the ritual feasts that took place in the building.
Keywords: Epigraphy; Palaeohispanic languages; Iberian Archaeology; Religion; Romanization